Chain Writing Method and Media Picture in English Descriptive Texts Learning - Anggun Pertiwi; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2019)
The aim of this research was to analyze: 1) the use of chain writing method and media picture in English descriptive text learning. 2) the advantages and disadvantages of chain writing method and media picture in English descriptive text learning. 3) the results of the use of chain writing method and media picture in English descriptive text learning. The research method is a case study. The subjects of this research were 5 students. Observation, interview and documentation were used as the instruments of eliciting the data. The results show that: 1) the use of chain writing method and media picture in English descriptive text learning worked well, that was students actively involved in learning corresponding lesson plan. 2) chain writing method and media picture in English descriptive text learning each has its advantages and disadvantages. 3) The implementation by using chain writing method and media picture in English descriptive text learning showed very good results, in cognitive, affective, psychomotor aspects.